Evaluation of Wound-Healing Activity of Hydrogel Extract of Sansevieria trifasciata Leaves (Asparagaceae) - Nia Yuniarsih; Himyatul Hidayah; Neni Sri Gunarti; Anggun Hari Kusumawati; Farhamzah Farhamzah; Asman Sadino; Maulana Yusuf Alkandahri (Advances in Pharmacological and Pharmaceutical Sciences)
For centuries, communities have used medicinal plants to treat various diseases, such as Sansevieria trifasciata (Asparagaceae), for wound healing. However, a study on the wound-healing activity of this plant has not been conducted. Therefore, this study aimed to evaluate the hydrogel formulations of S. trifasciata extract (HESt) and its activity in wound healing. The HESt formulations were subjected to physical examination, pH measurement, spreading coefficient, rheological study, stability test, and wound-healing activity. Furthermore, the HPMC and carbopol 940 gel-forming agents were used to obtain this formulation. In the incision wound model, the experiment was divided into 5 groups, each consisting of 4 mice. Groups 1 and 2 served as a negative and positive control (octenidine gel), while 3, 4, and 5 were given HESt formulations of 15%, 20%, and 25% (w/w), respectively, for 15 days. Based on the wound healing activity test, HESt 20% and 25% (w/w) groups showed significant (p < 0.05) wound closure area on day 4 and from day 2 to 16. However, the HESt 15% (w/w) group showed no significant difference in wound-healing activity but had a higher closure than the negative control. Based on the evaluation of the hydrogel, all HESt formulations were reported to have fulfilled the standard requirements. The HESt formulations were also reported to be stable at various temperatures in the stability test. Therefore, S. trifasciata leaves extract has the potential to be developed as a wound-healing drug derived from herbal plants formulated into hydrogel preparations.